2346. Severe Head and Neck Infections Following Influenza Virus Infection in Children. (26th November 2018) - Foster, Catherine; Kaplan, Sheldon L
Abstract: Background: Seasonal influenza infection is associated with secondary bacterial complications involving the upper and lower respiratory tract. However, the association of influenza infection with secondary severe or complicated head and neck infections is not appreciated. Methods: We performed a retrospective review of pediatric patients hospitalized at Texas Children's Hospital with bacterial head or neck infections following influenza infection from October 2017 to March 2018. We queried the infectious diseases consult database using the search terms: orbital cellulitis, mastoiditis, retropharyngeal abscess, peritonsillar abscess, deep neck abscess, subdural empyema, Lemierre's syndrome, and Pott's puffy tumor. Based upon medical records review and ICD-10 codes, patients were included in this study if they had a head or neck infection and reported a positive rapid influenza diagnostic test within 30 days preceding hospital admission. Results: We identified 44 patients with head or neck infections, of which 6 patients met inclusion criteria (table). The male-to-female ratio was 5:1 and the median age was 11.6 years (range 1.7–13.9 years). Most patients were diagnosed with influenza during a period of high influenza activity and the median time from influenza diagnosis to hospital admission was 4.5 days (range 1–6 days). One patient had received seasonal influenza vaccination. Patients had a wide range of infections, including orbital cellulitis (3), retropharyngeal abscess (2), and 1 of each of the following: Lemierre's syndrome, peritonsillar abscess, Pott's puffy tumor, and subdural empyema; 4 also had sinusitis. A causative pathogen was established in four cases: methicillin-resistant Staphylococcus aureus, Streptococcus anginosus group, S. pyogenes, and S. intermedius . The median duration of hospitalization was 22 days (range 5–35 days) and treatment duration ranged from 3.5 to 6 weeks. All patients completed antibiotic treatment successfully and had favorable outcomes. Conclusion: We suggest that complicated bacterial head and neck infections may represent an under recognized co-infection or secondary complication of infection with influenza virus, further stressing the importance of prevention and treatment of influenza infection. Disclosures: All authors: No reported disclosures.